Draft Annual Plan Proposals (1973-74) Government of Bihar Planning Department - Planning Commission (Planning Commission, 1973)
Bihar is caught up in the vicious circle of low incomes, low savings, low investments and low levels of development. In the last few years, attempts have been made to break up this vicious circle by stepping up investments in the economy and other activities. But these have not had the desired effects so far principally because investment efforts have been kept limited, among others, to the financial resources raised by the State. Since the under-developed character of the State itself severely restricts its capacities to raise resources, the circle continues unbroken.
Government of Bihar, Planning Department